MENINGKATKAN KETERAMPILAN BAHASA INGGRIS DAN LONTARA MAKASSAR PESERTA DIDIK KELAS VI B UPT SPF SD INPRES BONTOMANAI MELALUI KARTU AJAIB - Fatima Gita Mutmaina; Husnaeni; Asmirah Khusnul Yuliana; Andini; Harliwan; Dewi Mitra Maulidyah; Irmawati; A. Mulkaida Istiqomah; Alifah Dhiah Qanifah Lestari; Fachrul Achsan Saputra; Maria Ulviani (STKIP Subang, 2024)
BISAMAKI (Learning English and Makassar Lontara Through Magic Cards) is an activity to improve students' understanding of English and Makassar Lontara. The Lontara script is a traditional script of the Makassar community. While the introduction of English is also needed because it is still taught in a number of schools in South Sulawesi as part of the local content. English is a foreign language that can help students compete in the global world in the future. This project aims to equip students with language skills for both global communication and local cultural preservation. The stages carried out in the implementation of this project are; 1) Conducting field surveys and socialization, 2) Conducting initial assessments, 3) Program Planning, 4) Developing Educational Materials, 5) Program Implementation, 6) Learning Evaluation. The results of this activity received a positive response from the residents of UPT SPF SDI Bontomanai, through the use of magic cards proven effective in creating interactive and enjoyable learning experiences. Active involvement during project activities is one of the keys to project success where students not only learn the language but are also actively involved in the learning process.